Socialization of AKMI Policy as a Catalyst for Enhancing Students' Reading Interest - Akhmaliah Siti Nailan; Ana Anisa; Asri Khoirunnisa; Dedeh Sariah; Wahyu Hidayat (Journal of Education Reseach and Evaluation, 2025)
This research is motivated by the lack of socialization of the Indonesia Madrasah Competency Assessment (AKMI) policy which causes problems in its implementation, especially related to students' interest in reading. This study aims to determine the relationship between the socialization of AKMI policies and students' interest in reading. This study uses a quantitative method with a type of correlational research. Data was collected through interviews and questionnaires compiled based on indicators of policy socialization and reading interest. The results of the study showed that policy socialization was relatively good, with a percentage of 71.15%, and students' reading interest was also in the good category with a percentage of 65.33%. Correlation analysis showed a significant positive relationship between the socialization of AKMI policies and students' reading interest, with a correlation coefficient of 0.450 which was included in the medium category. The influence of AKMI policy socialization on students' reading interest reached 25%, while the remaining 75% was influenced by other factors such as student learning outcomes, teacher ability, and student intellectual level. In conclusion, there is a significant positive relationship between the socialization of AKMI policies and students' interest in reading. Effective implementation of AKMI policies can increase reading literacy and students' interest in reading through various literacy programs developed in madrasas.